Permafrost degradation amplifies infrastructure-related inequalities across the Qinghai-Tibet Plateau - Xinlong Du; Chunling Zhang; Yunjie Jia; Yuguo Wei; Jinyue Song; Mei Mu; Xiaoqing Peng; Zongxing Li; Peng Zhang; Lin Liu; Zhuoxuan Xia; Rongkun Liu; et al. (Global Environmental Change, 2026)

Recombinant bovine αs1-casein as an enhanced precursor for sleep-promoting peptides: A structural, peptidomic, and molecular docking study - Long Pan; Lin-Lin Ding; Meng-Jia Song; Xiang-Li Mu; Ai-Mei Liao; Yin-Chen Hou; Ji-Hong Huang; Guang-Hai Yu (Food Bioscience, 2026)

Decoding novel umami peptides from soy protein isolate hydrolysate: Mechanistic insights via multisensory techniques, machine learning and molecular docking - Xueying Song; Dipeng Mei; Yihan Mu; Peng Cheng; Siliang Wu; Chenchen Cao; Guowan Su (Food Bioscience, 2026)

Suicide attempt risk among patients receiving methylphenidate: a retrospective cohort study - Tai-Long Pan; Li-Chi Chen; Ju-Wei Hsu; Ya-Mei Bai; Shih-Jen Tsai; Tzeng-Ji Chen; Mu-Hong Chen (Psychopharmacology, 2026)
Background Methylphenidate may reduce suicide risk among patients with attention-deficit hyperactivity disorder. Several studies have noted that the association between methylphenidate use and suicidality is weakening. Methods Data were collected from Taiwan’s National Health Insurance Research Database to assess the association between methylphenidate exposure and suicide attempt risk across two exposure periods (main analysis: 2001–2002; duplication analysis: 2004–2005). We compared suicide attempt risk between patients who initiated methylphenidate treatment and those with no recorded psychiatric treatment or methylphenidate exposure during the same period. Results In both the main and duplication analyses, patients receiving methylphenidate exhibited a higher subsequent risk of suicide attempts than unexposed individuals. A duration–response pattern was observed in both cohorts: the hazard ratio of suicide attempts declined with longer cumulative methylphenidate use, from 1.60/1.84 for < 30 days to 1.45/1.65 for ≥ 180 days. Because hazard ratios were closely aligned across 2001–2002 and 2004–2005, the association of methylphenidate with reduced suicide attempt risk did not appear to decrease over time. Discussion Longer use of methylphenidate was associated with a lower risk of subsequent suicide attempts among patients in Taiwan receiving methylphenidate. The beneficial effect of methylphenidate on suicide risk remained consistent over time.

Scoparone alleviates cisplatin-induced acute kidney injury by inhibiting 5-lipoxygenase-mediated ferroptosis - Congcong Dai; Shuting Huang; Na Huang; Suwan Mu; Suwang Liu; Minhui Xie; Jing Mei; Yuhong Tang; Honghao Yu; Pengpeng Yue; Yong Li; Jun Ou (Toxicology and Applied Pharmacology, 2026)

Shorter to be effective: subanesthetic-dose ketamine infusion reduces the global and regional path length of brain functional connectivity in patients with treatment-resistant depression and suicidal ideation - Wei-Chen Lin; Li-Kai Cheng; Tung-Ping Su; Li-Fen Chen; Pei-Chi Tu; Cheng-Ta Li; Ya-Mei Bai; Shih-Jen Tsai; Mu-Hong Chen (Psychopharmacology, 2026)

Corrigendum to ‘ORF603 derived from AcMNPV plays entirely opposite roles in regulating BmNPV infection’ [Pesticide Biochemistry and Physiology 220 (2026) 107056] - Xin-yi Ding; Jiang-zhi Su; Yu-shuo Song; Wen-Jing Yu; Zuo-min Shao; Sheng Qin; Xia Sun; Xue-yang Wang; Xiao-mei Ma; Mu-wang Li (Pesticide Biochemistry and Physiology, 2026)

ORF603 derived from AcMNPV plays entirely opposite roles in regulating BmNPV infection - Xin-yi Ding; Jiang-zhi Su; Yu-shuo Song; Wen-Jing Yu; Zuo-min Shao; Sheng Qin; Xia Sun; Xue-yang Wang; Xiao-mei Ma; Mu-wang Li (Pesticide Biochemistry and Physiology, 2026)

Harnessing grain boundary pinning: A triple synergistic strategy for ultra-stable, sintering-resistant CaO-based CO₂ sorbents - Zeyi Wang; Yuanqiong Mu; Zhipeng Wang; Mei Zhang; Min Guo (Chemical Engineering Journal, 2026)

A smartphone-controlled microfluidic platform for rapid, sample-to-answer HLA-B*58:01 genotyping via LNA-enhanced duplex RPA - Xinpei Pang; Zhubing Lei; Xiang Mu; Shuang Wu; Wen-Fei Dong; Qian Mei (Chemical Engineering Journal, 2026)

AI-driven discovery of natural product-derived FAK1 inhibitors for idiopathic pulmonary fibrosis - Xing-Yi Chen; Mei-Hong Lu; Bin Li; Ya Zhou; Li Liu; Hao Yang; Qiu-Yu Wang; Lin Chang; Yu-Lan Zhao; Dong-Mei Wang; Bin Li; Ben-Rong Mu (Molecular Diversity, 2026)

Species-dependent growth rates regulate community biomass under long-term warming and wetting in alpine meadow on the Qinghai-Tibet Plateau - Mingming Shi; Cuicui Mu; Bingrong Zhou; Xiaodong Li; Yunqiao Ma; Mei Mu; Jinyue Song; Xinlong Du; Huakun Zhou (Plant and Soil, 2026)

A novel antioxidant peptide DD12 (DWPDARGIWHND) derived from dry cured ham alleviates H2O2-induced oxidative damage via the Keap1-Nrf2-ARE pathway - Ying-dao Nan; Si-qi Chen; Guan-hao Li; Ting-yu Li; Bai-de Mu; Juan Wang; Jian Feng; Hong-mei Li; Chun-xiang Piao (Food Research International, 2026)

Trace carbonyls in water reuse: Structure-dependent multi-barrier penetration and enhanced deep mineralization via dual-radical oxidation synergism - Yun-Peng Wu; Qian-Yuan Wu; Zi-Bo Jing; Yu-Ming Tian; Jiang-Lei Xiong; Mu-Da Han; Sheng-Mei Li; Er-Dong Wang; Wen-Long Wang (Water Research, 2026)

Low-glutelin rice as a food-based strategy for protein restriction: Genetic development, structural engineering, and nutritional consequences - Ying Mei; Yuwei Hua; Yuxin Mu; Qiang Liu; Siqi Zhao; Xinbo Zhuang; Chao Ding; Liping Guo (Trends in Food Science & Technology, 2026)

Effects of taurine on immunity and ammonia metabolism in large-scale loach under ammonia stress - Ruo-Yu Zhou; Lu Chen; Meng-Yang Hu; Mu-Xi Li; Yu-Xuan Fei; Mei Huang; Yun-Long Zhang (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Research progress on exogenous substances and their mechanisms of action in alleviating low-temperature stress in plants - Jiayi Chen; Qian Zhou; Qiong Wu; Jun Yang; Bihui Huang; Wenli Mu; Qinshuang Mei; Heping Zhao; Haifang Hu; Fenglan Liu; Jing Guo; Huixin Zhao (Planta, 2026)

Aridity controls on the dominance of soil mineral-associated and particulate organic carbon in the Qinghai-Tibet Plateau - Hebin Liu; Mei Mu; Cuicui Mu; Kun Li; Yuguo Wei; Pengsi Lei; Fumei Liu; Xinlong Du; Shijie Li; Jianyu Li (Global and Planetary Change, 2026)

Biodegradation of unpretreated polypropylene microplastic and agricultural polypropylene film by a bacterium isolated from an oil reservoir - Sheng Jin Li; Yun Yang Wan; Zhe Ke Zhong; Ying Jia Zhu; Hong Mei Mu; Sheng Bao Shi (Journal of Environmental Chemical Engineering, 2025)

Predicting and interpreting nitrogen removal performance and functional microbial abundance of single-stage partial nitrification and anammox system using machine learning methods - Xiulin Mu; Fangxu Jia; Shengming Qiu; Yiran Li; Ning Mei; Xingcheng Zhao; Baohong Han; Xiangyu Han; Jingjing Zhang; Hong Yao (Bioresource Technology, 2025)

The critical role of mitophagy in cell senescence-mediated pulmonary fibrosis and potential therapeutic strategies - Xing-Yi Chen; Dong-Mei Wang; Ya Zhou; Li Liu; Tao Zhu; Zhao Ran; Mei-Hong Lu; Ben-Rong Mu (Molecular Biology Reports, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

Enhanced biodegradation of crude oil by phosphate-solubilizing bacteria Bacillus subtilis PSB-1: Overcoming soluble phosphorus deficiency - Xudong Wang; Zhuorong Du; Zhenzhen Li; Mei Liu; Jun Mu; Lijuan Feng; Zhi Chen; Qingguo Chen (Journal of Environmental Management, 2025)

Polyetheretherketone-based foam with low reflectivity and high electromagnetic interference shielding effectiveness suitable for harsh service environments - Liubo Liang; Tonghua Wu; Xiaohan Mei; Yu Bai; Chunqi Guo; Yanchao Yang; Guibin Wang; Shuling Zhang; Jianxin Mu (Chemical Engineering Journal, 2025)

Collaborative optimization method of cleaning operational performance and multiparameter online control system for combine harvesters - Tao Jiang; Zhuohuai Guan; Haitong Li; Min Zhang; Senlin Mu; Chongyou Wu; Mei Jin (Computers and Electronics in Agriculture, 2025)

Nitrogen uptake and nitrification in the Changjiang estuary - Xing Hou; Chongcong Liu; Guodong Song; Jinglong Mu; Wen Liang; Haoming Xu; Nian Wu; Wenqi Xu; Su Mei Liu (Marine Environmental Research, 2025)

Enhanced solid–gas-phase carbon dioxide photoreduction efficiency through in-situ growth of W18O49 on one-dimensional Nb2O5 nanofibers for forming well-connected S-scheme heterojunction - Yanxin Wang; Ran Tao; Yongqi Mu; Tianyang Piao; Jiale Li; Yong Mei; Xiaoxing Fan; Quanzhan Yang (Fuel, 2025)

Parkinson's Disease and the Microbiota-Gut-Brain Axis: Metabolites, Mechanisms, and Innovative Therapeutic Strategies Targeting the Gut Microbiota - Zhao Ran; Ben-Rong Mu; Dong-Mei Wang; Xin-Huang; Quan-Hong Ma; Mei-Hong Lu (Molecular Neurobiology, 2025)

Astaxanthin ameliorates high-carbohydrate diet-induced ER stress, immunosuppression and hepatic glucose metabolism through AMPK/autophagy pathway in Channa argus - Mu-Yang Li; Yun-Zhuo Liu; Xiu-Mei Chen; Xiao-Tian Niu; Lu Chen; Lei Zhao; Gui-Qin Wang (Aquaculture, 2025)

Enhanced electrochemical performance of NCM811-based batteries by using a multifunctional electrolyte additive - Aijia Wei; Shuxing Mei; Jinping Mu; Peng Liu; Xue Bai; Rui He; Xiaohui Li; Yuxin Niu; Lihui Zhang; Zhenfa Liu; Lei Wang (Chemical Engineering Journal, 2025)

High UV-shielding polyvinyl alcohol/chitosan-based transparent bioplastic film for food preservation - Mei Bao; Honglei Mu; Ben Niu; Ruiling Liu; Huizhi Chen; Hangjun Chen; Lishu Wang; Yanchao Han; Guannan Wang; Haiyan Gao (Food Packaging and Shelf Life, 2025)

Model test and numerical simulation of open caisson foundation under long-term lateral loading - Baogang Mu; Xu Ling; Weifeng Zheng; Guoxiong Mei; Pengpeng Ni (Ocean Engineering, 2024)

Effect of Foliar Application of Selenite On Organic Se and Antioxidant Activity in Kiwifruit - Yun-mei Lu; Mao Mu; Li-ai Wang; Ren-hua Huang (Applied Fruit Science, 2024)

The influence of North Atlantic sea surface temperature fluctuations on the climate of the Qinling-Bashan Mountains, China based on a 250 year tree-ring record - Qiufang Cai; Mei Xie; Yu Liu; Congxi Fang; Zhixin Hao; Meng Ren; Qiuyue Zhou; Yikui Mu; Yufei Chen (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Exploring the novel antioxidant peptides in low-salt dry-cured ham: Preparation, purification, identification and molecular docking - Ying-dao Nan; Bai-de Mu; Chang-xin Ge; Si-qi Chen; Ming-xun Cui; Hong-mei Li; Chang-cheng Zhao; Juan Wang; Chun-xiang Piao; Guan-hao Li (Food Chemistry, 2024)

Exploring lipid digestion discrepancies between preterm formula and human milk: Insights from in vitro gastrointestinal digestion and the impact of added milk fat - Ning Wang; Sen Yang; Guang-Qing Mu; Fang Qian; Xue-Mei Zhu (Food Research International, 2024)

Long-term exposure to major constituents of fine particulate matter and neurodegenerative diseases: A population-based survey in the Pearl River Delta Region, China - Qi-Zhen Wu; Hui-Xian Zeng; John Andersson; Anna Oudin; Katja M. Kanninen; Mu-Wu Xu; Shuang-Jian Qin; Qing-Guo Zeng; Bin Zhao; Mei Zheng; Nanxiang Jin; Wei-Chun Chou; et al. (Journal of Hazardous Materials, 2024)

A MYB transcription factor GhTT2 of Gossypium hirsutum regulates proanthocyanidin accumulation and improves osmotic tolerance in Arabidopsis - Jun Mei; Rongrong Mu; Qingqing Niu; Huimin Zhu; Ruoxi Chen; Xiaomiao Cai; Meng Miao; Dongliang Yu; Liping Ke; Yuqiang Sun (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

The major role of glucocorticoid receptor (GR) in astaxanthin alleviates immune stress in Channa argus lymphocyte - Xiao-Tian Niu; Chuang Sun; Lei Zhao; Xiu-Mei Chen; Gui-Qin Wang; Mu-Yang Li (Aquaculture, 2024)

Multiple isotopes decipher the nitrogen cycle in the cascade reservoirs and downstream in the middle and lower Yellow River: Insight for reservoir drainage period - Jinglong Mu; Shuai Ding; Su Mei Liu; Guodong Song; Xiaoyan Ning; Xiaotong Zhang; Wenqi Xu; Hongmei Zhang (Science of The Total Environment, 2024)

Enhanced carbon dioxide sequestration and Cr detoxification: Direct carbonation of AOD slag with additives under ambient conditions - Haolei Wang; Gang Zhou; Yuanqiong Mu; Mei Zhang; Min Guo (Journal of Cleaner Production, 2024)

Genetic architecture of ecological divergence between Oryza rufipogon and Oryza nivara - Qing‐Lin Meng; Cheng‐Gen Qiang; Ji‐Long Li; Mu‐Fan Geng; Ning‐Ning Ren; Zhe Cai; Mei‐Xia Wang; Zi‐Hui Jiao; Fu‐Min Zhang; Xian‐Jun Song; Song Ge (Molecular Ecology, 2024)
Ecological divergence due to habitat difference plays a prominent role in the formation of new species, but the genetic architecture during ecological speciation and the mechanism underlying phenotypic divergence remain less understood. Two wild ancestors of rice ( Oryza rufipogon and Oryza nivara ) are a progenitor‐derivative species pair with ecological divergence and provide a unique system for studying ecological adaptation/speciation. Here, we constructed a high‐resolution linkage map and conducted a quantitative trait locus (QTL) analysis of 19 phenotypic traits using an F 2 population generated from a cross between the two Oryza species. We identified 113 QTLs associated with interspecific divergence of 16 quantitative traits, with effect sizes ranging from 1.61% to 34.1% in terms of the percentage of variation explained (PVE). The distribution of effect sizes of QTLs followed a negative exponential, suggesting that a few genes of large effect and many genes of small effect were responsible for the phenotypic divergence. We observed 18 clusters of QTLs (QTL hotspots) on 11 chromosomes, significantly more than that expected by chance, demonstrating the importance of coinheritance of loci/genes in ecological adaptation/speciation. Analysis of effect direction and v ‐test statistics revealed that interspecific differentiation of most traits was driven by divergent natural selection, supporting the argument that ecological adaptation/speciation would proceed rapidly under coordinated selection on multiple traits. Our findings provide new insights into the understanding of genetic architecture of ecological adaptation and speciation in plants and help effective manipulation of specific genes or gene cluster in rice breeding.

Effects of electron acceptors and donors on anaerobic biodegradation of PAHs in marine sediments - Qingguo Chen; Zhenzhen Li; Yu Chen; Mei Liu; Qiao Yang; Baikang Zhu; Jun Mu; Lijuan Feng; Zhi Chen (Marine Pollution Bulletin, 2024)

Nutrient dynamics in the Yellow River -a case study of different reservoir regulation operations - Jinglong Mu; Hongmei Zhang; Su Mei Liu; Nian Wu; Guodong Song; Shuai Ding; Xiaotong Zhang (Journal of Hydrology, 2024)

Cellular localization and potential ligands of a novel scavenger receptor class B/CD36 protein homolog (Pt-SRB2) identified in the marine crab, Portunus trituberculatus - Su-Ming Zhou; Fang-Mei Lin; Chang-Kao Mu; Chun-Lin Wang; Qi-Cun Zhou; Peng Sun; Fei Yin (Fish & Shellfish Immunology, 2024)

Construction of and evaluation of the immune response to two recombinant pseudorabies viruses expressing the B119L and EP364R proteins of African swine fever virus - Xin-Mei Geng; Ying-Mu Xi; Xiang-Mei Huang; Yang-Lin Wang; Xu-Ying Wang; Kang Ouyang; Ying Chen; Zu-Zhang Wei; Yi-Feng Qin; Wei-Jian Huang (Archives of Virology, 2024)

Toxicity of common biocides used in aquaculture to embryos and larvae of Brachymystax tsinlingensis Li - Xing‐chen Guo; Zhi‐peng Chu; Rong‐qun Song; Zhen‐lu Wang; Rui‐jiao Li; Dong‐mei Xiong; Mu‐zi Zhang; Hai‐bo Jiang; Jian Shao (Journal of Fish Biology, 2024)
Brachymystax tsinlingensis Li is a threatened fish species endemic to China. With the problems of environmental factors and seeding breeding diseases, it is important to further improve the efficiency of seeding breeding and the basis of resource protection. This study investigated the acute toxicity of copper, zinc and methylene blue (MB) on hatching, survival, morphology, heart rate (HR) and stress behaviour of B. tsinlingensis . Eggs (diameter: 3.86 ± 0.07 mm, weight: 0.032 ± 0.004 g) of B. tsinlingensis were selected randomly from artificial propagation and developed from eye‐pigmentation‐stage embryos to yolk‐sac stage larvae (length: 12.40 ± 0.02 mm, weight: 0.03 ± 0.001 g) and exposed to different concentrations of Cu, Zn and MB for 144 h in a series of semi‐static toxicity tests. The acute toxicity tests indicated that the 96‐h median lethal concentration (LC 50 ) values of the embryos and larvae were 1.71 and 0.22 mg l −1 for copper and 2.57 and 2.72 mg l −1 for zinc, respectively, whereas the MB LC 50 after 144‐h exposure for embryos and larvae were 67.88 and 17.81 mg l −1 , respectively. The safe concentrations of copper, zinc and MB were 0.17, 0.77 and 6.79 mg l −1 for embryos and 0.03, 0.03 and 1.78 mg l −1 for larvae, respectively. Copper, zinc and MB treatments with concentrations greater than 1.60, 2.00 and 60.00 mg l −1 , respectively, led to a significantly low hatching rate and significantly high embryo mortality ( P −1 led to significantly high larvae mortality ( P P P B. tsinlingensis embryos or larvae might be more resistant to copper, zinc and MB than other members of the Salmonidae family, which benefits their resource protection and restoration.

Targeting mitophagy for neurological disorders treatment: advances in drugs and non-drug approaches - Xiong Yang; Yu Zhang; Jia-xin Luo; Tao Zhu; Zhao Ran; Ben-Rong Mu; Mei-Hong Lu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Thermokarst lake changes along the Qinghai-Tibet Highway during 1991–2020 - Mei Mu; Cuicui Mu; Pengsi Lei; Xiaoxiao Mo; Yuan Qiao; Xu Chen; Hebin Liu (Geomorphology, 2023)

Lactic acid bacteria with probiotic characteristics in fermented dairy products reduce cow milk allergy - Zi-Hao Guo; Qi Wang; Jing-Hong Zhao; Yun-Peng Xu; Guang-Qing Mu; Xue-Mei Zhu (Food Bioscience, 2023)

Modulating the coordination environment of Co single-atom catalysts through sulphur doping to efficiently enhance peroxymonosulfate activation for degradation of carbamazepine - Wei Zhang; Mu Li; Jingwen Luo; Guan Zhang; Lin Lin; Feiyun Sun; Mei Li; Zijun Dong; Xiao-yan Li (Chemical Engineering Journal, 2023)

Carbon loss and emissions within a permafrost collapse chronosequence - Mei Mu; Cuicui Mu; Hebin Liu; Haiteng Chi; Yongji Zhu; Jianguo Shang; Chengyan Fan; Xiaodong Wu; Guofei Zhang (CATENA, 2023)

Antimony(III) removal by biogenic manganese oxides formed by Pseudomonas aeruginosa PA-1: kinetics and mechanisms - Qing Li; Yun He; Aijiang Yang; Xia Hu; Fang Liu; Jincheng Mu; Shixue Mei; Lin-Ping Yang (Environmental Science and Pollution Research, 2023)

Eugenilones A−N: sesquiterpenoids from the fruits of Eugenia uniflora - Mu Chen; Run-Qiang Chen; Yuan Guo; Jian-Xin Chen; Qian Jin; Mei-Hong Chen; Bo-Yong Chen; Zheng-Chao Tu; Wen-Cai Ye; Lei Wang (Phytochemistry, 2023)

Preparation of cellulose nanofibers from potato residues by ultrasonication combined with high-pressure homogenization - Xiaowen Liu; Hongnan Sun; Taihua Mu; Marie Laure Fauconnier; Mei Li (Food Chemistry, 2023)

High carbon emissions from thermokarst lakes and their determinants in the Tibet Plateau - Cuicui Mu; Mei Mu; Xiaodong Wu; Lin Jia; Chenyan Fan; Xiaoqing Peng; Chien‐Lu Ping; Qingbai Wu; Cunde Xiao; Jianbao Liu (Global Change Biology, 2023)
Thermokarst lakes are potentially important sources of methane (CH 4 ) and carbon dioxide (CO 2 ). However, considerable uncertainty exists regarding carbon emissions from thermokarst lakes owing to a limited understanding of their patterns and motivators. In this study, we measured CH 4 and CO 2 diffusive fluxes in 163 thermokarst lakes in the Qinghai–Tibet Plateau (QTP) over 3 years from May to October. The median carbon emissions from the QTP thermokarst lakes were 1440 mg CO 2 m −2 day −1 and 60 mg CH 4 m −2 day −1 , respectively. The diffusive rates of CO 2 and CH 4 are related to the catchment land cover type. Sediment microbial abundance and hydrochemistry explain 51.9% and 38.3% of the total variance in CH 4 diffusive emissions, respectively, while CO 2 emissions show no significant relationship with environmental factors. When upscaling carbon emissions from the QTP thermokarst lakes, the annual average CH 4 release per lake area is equal to that of the pan‐Arctic region. Our findings highlight the importance of incorporating in situ observation data with different emission pathways for different land cover types in predicting carbon emissions from thermokarst lakes in the future.

Dough rheological properties, texture, and structure of high-moisture starch hydrogels with different potassium-, and calcium-based compounds - Hong-Yuan Zhang; Hong-Nan Sun; Meng-Mei Ma; Tai-Hua Mu (Food Hydrocolloids, 2023)

Leaf and Soil Phosphatases and the Correlations with Leaf P Resorption of Lucerne Under P Fertilization and Irrigation - Mei Yang; Yixiao Lu; Le Mu; Huimin Yang (Journal of Soil Science and Plant Nutrition, 2023)

Indole acetylated high-amylose maize starch: Synthesis, characterization and application for amelioration of colitis - Yingying Song; Xinyan Qu; Mei Guo; Qiongzheng Hu; Yan Mu; Na Hao; Yunbo Wei; Quanbo Wang; Charles R. Mackay (Carbohydrate Polymers, 2023)

In-situ Fe/Ti doped amine-grafted silica aerogel from fly ash for efficient CO2 capture: Facile synthesis and super adsorption performance - Lingyuan Fan; Yuanqiong Mu; Jiali Feng; Fangqin Cheng; Mei Zhang; Min Guo (Chemical Engineering Journal, 2023)

Doping engineering of carrier transporting layers for ambient-air-stable lead-free rudorffite solar cells prepared by thermal-assisted doctor blade coating - Kai-Chi Hsiao; Yen-Fu Yu; Ching-Mei Ho; Meng-Huan Jao; Yu-Hsiang Chang; Shih-Hsuan Chen; Yin-Hsuan Chang; Wei-Fang Su; Kun-Mu Lee; Ming-Chung Wu (Chemical Engineering Journal, 2023)

Xinfangfangia pollutisoli sp. nov., Isolated from Clopyralid-Contaminated Soil - Yang Mu; Jia-Yi Peng; Hui-Ping Wang; Yue Song; Hong-Mei Wang; Qing Chen; Kai Chen (Current Microbiology, 2022)

Difructose anhydride III: a 50-year perspective on its production and physiological functions - Mei Cheng; Hao Wu; Wenli Zhang; Wanmeng Mu (Critical Reviews in Food Science and Nutrition, 2022)

Quick mapping and characterization of a co-located kernel length and thousand-kernel weight-related QTL in wheat - Xiangru Qu; Cong Li; Hang Liu; Jiajun Liu; Wei Luo; Qiang Xu; Huaping Tang; Yang Mu; Mei Deng; Zhien Pu; Jun Ma; Qiantao Jiang; et al. (Theoretical and Applied Genetics, 2022)

Association of cognitive impairment and reduced cortical thickness in prefrontal cortex and anterior cingulate cortex with treatment-resistant depression - Mu-Hong Chen; Wan-Chen Chang; Pei-Chi Tu; Wei-Chen Lin; Cheng-Ta Li; Wen-Sheng Huang; Ya-Mei Bai; Shih-Jen Tsai; Tung-Ping Su (Brain Imaging and Behavior, 2022)

Historical Connectivity and Demography of the Ferocious Reef Crab, Eriphia ferox (Crustacea; Eriphiidae), Demonstrate That Taoyuan Algal Reef Is an Essential Population Source Along the East Taiwan Strait - Mu-Han Chen; Ya-Yi Huang; Bi-Ying Huang; Hernyi Justin Hsieh; Jen Nie Lee; Mei Lin Neo; Hironobu Fukami; Chaolun Allen Chen (Frontiers in Marine Science, 2022)
The east Taiwan Strait is largely fringed by sandy and muddy habitats. However, a massive algal reef made of crustose coralline algae has been found along the coast off Taoyuan city in northwestern Taiwan. The porous structure of Taoyuan Algal Reef harbors high abundance and diversity in marine organisms, including the ferocious reef crab, Eriphia ferox . Such a pivotal geographic location and unique ecological features make Taoyuan Algal Reef a potential stepping stone connecting biotic reefs in the east Taiwan Strait, South China Sea to the south, and even the high latitude of Japan to the north. In this study, we examined the population connectivity and historical demography of E. ferox by analyzing mitochondrial cytochrome oxidase I (COI) fragments of 317 individuals sampled from 21 localities in the northwestern Pacific. Our analyses of haplotype network and pairwise F ST comparisons revealed a lack of phylogeographical structure among E. ferox populations, implying the existence of a migration corridor connecting the South and East China Seas through the east Taiwan Strait. Multiple lines of evidence, including significant values in neutrality tests, unimodally shaped mismatch distributions, and Bayesian skyline plots elucidated the rapid population growth of E. ferox following the sea-level rise after Last Glacial Maximum (ca. 2–10 Ka). Such demographic expansion in E. ferox coincided with the time when Taoyuan Algal Reef started to build up around 7,500 years ago. Coalescent migration analyses further indicated that the large and continuous E. ferox population exclusively found in Datan Algal Reef, the heart of Taoyuan Algal Reef, was a source population exporting migrants both northward and southward to the adjacent populations. The bidirectional gene flow should be attributed to larval dispersal by ocean currents and secondary contact due to historical population expansion. Instead of serving as a stepping stone, our results support that Taoyuan Algal Reef is an essential population source for biotic reef-associated species along the east Taiwan Strait, and highlight the importance of conserving such a unique ecosystem currently threatened by anthropogenic development.

Identification and functional analysis of a pollen fertility-associated gene GhGLP4 of Gossypium hirsutum L. - Hongli Zheng; Rongjia Wang; Qimeng Jiang; Diandian Zhang; Rongrong Mu; Yihan Xu; Vitalis E. Nnaemeka; Jun Mei; Yanyan Zhao; Fangfang Cai; Dongliang Yu; Yuqiang Sun; et al. (Theoretical and Applied Genetics, 2021)

Proton Pump Inhibitor Exposure and Acute Myocardial Infarction Risk: A Nested Cohort Study - Hsiang-Jung Tseng; Chih-Ming Cheng; Shih-Jen Tsai; Wei-Chen Lin; Ya-Mei Bai; Chia-Fen Tsai; Tung-Ping Su; Cheng-Ta Li; Tzeng-Ji Chen; Mu-Hong Chen (Cardiovascular Toxicology, 2021)

Fibroblast Growth Factor 9 Stimulates Neuronal Length Through NF-kB Signaling in Striatal Cell Huntington’s Disease Models - Issa Olakunle Yusuf; Hsiu-Mei Chen; Pei-Hsun Cheng; Chih-Yi Chang; Shaw-Jenq Tsai; Jih-Ing Chuang; Chia-Ching Wu; Bu-Miin Huang; H. Sunny Sun; Chuan-Mu Chen; Shang-Hsun Yang (Molecular Neurobiology, 2021)

Interest-activity symptom severity predicts response to ketamine infusion in treatment-resistant depression - Mu-Hong Chen; Wei-Chen Lin; Hui-Ju Wu; Ya-Mei Bai; Cheng-Ta Li; Shih-Jen Tsai; Chen-Jee Hong; Pei-Chi Tu; Tung-Ping Su (Psychopharmacology, 2021)

Pseudomonas aeruginosa antitoxin HigA functions as a diverse regulatory factor by recognizing specific pseudopalindromic DNA motifs - Yingjie Song; Guihua Luo; Yibo Zhu; Tao Li; Changcheng Li; Lihui He; Ninglin Zhao; Chang Zhao; Jing Yang; Qin Huang; Xingyu Mu; Xinyue Tang; et al. (Environmental Microbiology, 2021)
Summary Type II toxin‐antitoxin (TA) systems modulate many essential cellular processes in prokaryotic organisms. Recent studies indicate certain type II antitoxins also transcriptionally regulate other genes, besides neutralizing toxin activity. Herein, we investigated the diverse transcriptional repression properties of type II TA antitoxin PaHigA from Pseudomonas aeruginosa . Biochemical and functional analyses showed that PaHigA recognized variable pseudopalindromic DNA sequences and repressed expression of multiple genes. Furthermore, we presented high resolution structures of apo‐PaHigA, PaHigA‐P higBA and PaHigA‐P pa2440 complex, describing how the rearrangements of the HTH domain accounted for the different DNA‐binding patterns among HigA homologues. Moreover, we demonstrated that the N‐terminal loop motion of PaHigA was associated with its apo and DNA‐bound states, reflecting a switch mechanism regulating HigA antitoxin function. Collectively, this work extends our understanding of how the PaHigB/HigA system regulates multiple metabolic pathways to balance the growth and stress response in P. aeruginosa and could guide further development of anti‐TA oriented strategies for pathogen treatment.

QTL mapping and validation of bread wheat flag leaf morphology across multiple environments in different genetic backgrounds - Yang Tu; Hang Liu; Jiajun Liu; Huaping Tang; Yang Mu; Mei Deng; Qiantao Jiang; Yaxi Liu; Guoyue Chen; Jirui Wang; Pengfei Qi; Zhien Pu; et al. (Theoretical and Applied Genetics, 2021)

A novel, validated, and plant height-independent QTL for spike extension length is associated with yield-related traits in wheat - Cong Li; Huaping Tang; Wei Luo; Xuemei Zhang; Yang Mu; Mei Deng; Yaxi Liu; Qiantao Jiang; Guoyue Chen; Jirui Wang; Pengfei Qi; Zhien Pu; et al. (Theoretical and Applied Genetics, 2020)

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

Creation of fertility-restored materials for Ogura CMS in Brassica oleracea by introducing Rfo gene from Brassica napus via an allotriploid strategy - Hai-long Yu; Zhi-yuan Li; Wen-jing Ren; Feng-qing Han; Li-mei Yang; Mu Zhuang; Hong-hao Lv; Yu-mei Liu; Zhi-yuan Fang; Yang-yong Zhang (Theoretical and Applied Genetics, 2020)
Key message Ogura CMS fertility-restored materials, with 18 chromosomes, normal seed setting, stable fertility and closer genetic background to the parent Chinese kale, were successfully developed in B. oleracea via a triploid strategy for the first time. Abstract Ogura cytoplasmic male sterility (CMS) is the most widely used sterile type in seed production for commercial hybrids of Brassica oleracea vegetables. However, the natural Ogura CMS restorer line has not been found in B. oleracea crops. In this study, the triploid strategy was used with the aim to create euploid B. oleracea progenies with the Rfo gene. The allotriploid AAC hybrid YL2 was used as a male parent to backcross with Ogura CMS Chinese kale. After successive backcrosses, the BC 2 Rfo -positive individual 16CMSF2-11 and its BC 3 progenies, with 18 chromosomes, were developed, which were morphologically identical to the parent Chinese kale. Compared with F 1 and BC 1 plants, it showed stable fertility performance, and regular meiosis behavior and could produce seeds normally under natural pollination. The genomic composition analysis of Rfo -positive progenies by using molecular markers showed that more than 87% of the C-genome components of BC 3 Rfo -progenies recovered to the parent Chinese kale, while most or all of the A n -genome segments were lost in 16CMSF2-11 and its progenies. The results suggested that the genetic background of Rfo -positive individuals was closer to that of the parent Chinese kale along with backcrossing. Hereof, the Ogura CMS fertility-restored materials of Chinese kale were successfully created via triploid strategy for the first time, providing a bridge for utilizing the Ogura CMS B. oleracea germplasm in the future. Moreover, our study indicates that the triploid strategy is effective for transferring genes from B. napus into B. oleracea .

The anti-inflammatory drug dimethyl itaconate protects against colitis-associated colorectal cancer - Qian Wang; Xin Ling Li; Yan Mei; Jia-Chong Ye; Wei Fan; Guang-Hui Cheng; Mu-Sheng Zeng; Guo-Kai Feng (Journal of Molecular Medicine, 2020)

A novel, major, and validated QTL for the effective tiller number located on chromosome arm 1BL in bread wheat - Jiajun Liu; Huaping Tang; Xiangru Qu; Hang Liu; Cong Li; Yang Tu; Shuiqing Li; Ahsan Habib; Yang Mu; Shoufeng Dai; Mei Deng; Qiantao Jiang; et al. (Plant Molecular Biology, 2020)

Vitamin D receptor gene methylation in patients with hand, foot, and mouth disease caused by enterovirus 71 - Ya-Ping Li; Hui-Ling Deng; Wen-Jun Wang; Mu-Qi Wang; Mei Li; Yu-Feng Zhang; Jun Wang; Shuang-Suo Dang (Archives of Virology, 2020)

Anti-hypertensive effects of Radix Rehmanniae and its active ingredients - Chiu-Haw Chao; Jue-Liang Hsu; Mu-Fen Chen; Ya-Hu Shih; Chia-Hui Lee; Mei-Li Wu; Chi-I Chang (Natural Product Research, 2020)

Combined effect of polymorphisms of MTHFR and MTR and arsenic methylation capacity on developmental delay in preschool children in Taiwan - Yu-Mei Hsueh; Ying-Chin Lin; Chi-Jung Chung; Ya-Li Huang; Ru-Lan Hsieh; Pai-Tsang Huang; Mei-Yi Wu; Horng-Sheng Shiue; Ssu-Ning Chien; Chih-Ying Lee; Ming-I. Lin; Shu-Chi Mu; et al. (Archives of Toxicology, 2020)

Acceleration of thaw slump during 1997–2017 in the Qilian Mountains of the northern Qinghai-Tibetan plateau - Cuicui Mu; Jianguo Shang; Tingjun Zhang; Chengyan Fan; Shufa Wang; Xiaoqing Peng; Wen Zhong; Feng Zhang; Mei Mu; Lin Jia (Landslides, 2020)

Correction to: Identification and validation of a major and stably expressed QTL for spikelet number per spike in bread wheat - Jian Ma; Puyang Ding; Jiajun Liu; Ting Li; Yaya Zou; Ahsan Habib; Yang Mu; Huaping Tang; Qiantao Jiang; Yaxi Liu; Guoyue Chen; Jirui Wang; et al. (Theoretical and Applied Genetics, 2020)

Identification and validation of a major and stably expressed QTL for spikelet number per spike in bread wheat - Jian Ma; Puyang Ding; Jiajun Liu; Ting Li; Yaya Zou; Ahsan Habib; Yang Mu; Huaping Tang; Qiantao Jiang; Yaxi Liu; Guoyue Chen; Jirui Wang; et al. (Theoretical and Applied Genetics, 2019)

MicroRNA transcriptome analysis of poly I:C-stimulated and PRRSV-infected porcine alveolar macrophages - Junjing Wu; Ziyun Ji; Mu Qiao; Xianwen Peng; Huayu Wu; Zhongxu Song; Haizhong Zhao; Guisheng Liu; Fenge Li; Shuqi Mei (Journal of Applied Genetics, 2019)

Association of plasma folate, vitamin B12 levels, and arsenic methylation capacity with developmental delay in preschool children in Taiwan - Ying-Chin Lin; Chi-Jung Chung; Ya-Li Huang; Ru-Lan Hsieh; Pai-Tsang Huang; Mei-Yi Wu; Pui-Lam Ao; Horng-Sheng Shiue; Shiau-Rung Huang; Chien-Tien Su; Ming-I Lin; Shu-Chi Mu; et al. (Archives of Toxicology, 2019)

Measurement of urinary arsenic profiles and DNA hypomethylation in a case–control study of urothelial carcinoma - Chi-Jung Chung; Hui-Ling Lee; Chao-Hsiang Chang; Han Chang; Chiu-Shong Liu; Wei-Ting Jung; Huei-Ju Liu; Saou-Hsing Liou; Mu-Chi Chung; Yu-Mei Hsueh (Archives of Toxicology, 2019)

Experimental investigation on the optical remote sensing images of internal solitary waves with a smooth surface - Yuan Mei; Jing Wang; Songsong Huang; Haidi Mu; Xu Chen (Acta Oceanologica Sinica, 2019)

Effects of dietary Allium mongolicum Regel polysaccharide on growth, lipopolysaccharide-induced antioxidant responses and immune responses in Channa argus - Mu-Yang Li; Xin-Ming Zhu; Xiao-Tian Niu; Xiu-Mei Chen; Jia-Xin Tian; Yi-Di Kong; Dong-Ming Zhang; Lei Zhao; Gui-Qin Wang (Molecular Biology Reports, 2019)

Pedobacter pollutisoli sp. nov., Isolated from Tetrabromobisphenol A-Contaminated Soil - Yang Mu; Zhuang Ke; Chen-Xi Feng; Xiao-Wei Wang; Xiao-Wen Wang; Hong-Mei Wang; Qing Chen; Jian He (Current Microbiology, 2019)

Atorvastatin ameliorates the contractile dysfunction of the aorta induced by organ culture - Feng Zhou; Fang Rao; You-Qing Deng; Hui Yang; Su-Juan Kuang; Fei-Long Wu; Shu-Lin Wu; Yu-Mei Xue; Xiao-Mu Wu; Chun-Yu Deng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Anomalous gray matter structural networks in recent onset post-traumatic stress disorder - Shun Qi; Yun-Feng Mu; Long-Biao Cui; Jian Zhang; Fan Guo; Qing-Rong Tan; Mei Shi; Kang Liu; Yi-Bin Xi; Nan-Yin Zhang; Xiao-Liang Zhang; Yong He; et al. (Brain Imaging and Behavior, 2018)

Roles of flotillins in tumors - Xu-xu Liu; Wei-dong Liu; Lei Wang; Bin Zhu; Xiao Shi; Zi-xuan Peng; He-cheng Zhu; Xing-dong Liu; Mei-zuo Zhong; Dan Xie; Mu-sheng Zeng; Cai-ping Ren (Journal of Zhejiang University-SCIENCE B, 2018)

Long-term perceptions of outdoor thermal environments in an elementary school in a hot-humid climate - Wen-Mei Shih; Tzu-Ping Lin; Ning-Xin Tan; Mu-Hsien Liu (International Journal of Biometeorology, 2017)

Recessive male sterility in cabbage (Brassica oleracea var. capitata) caused by loss of function of BoCYP704B1 due to the insertion of a LTR-retrotransposon - Jia-lei Ji; Li-mei Yang; Zhi-yuan Fang; Mu Zhuang; Yang-yong Zhang; Hong-hao Lv; Yu-mei Liu; Zhan-sheng Li (Theoretical and Applied Genetics, 2017)

Morphological and molecular characterization of the second backcross progenies of Ogu-CMS Chinese kale and rapeseed - Hai-long Yu; Zhi-yuan Li; Li-mei Yang; Yu-mei Liu; Mu Zhuang; Lu-gang Zhang; Hong-hao Lv; Zhan-sheng Li; Feng-qing Han; Xiao-ping Liu; Zhi-yuan Fang; Yang-yong Zhang (Euphytica, 2017)

NOX2 Mediated-Parvalbumin Interneuron Loss Might Contribute to Anxiety-Like and Enhanced Fear Learning Behavior in a Rat Model of Post-Traumatic Stress Disorder - Fang-fang Liu; Lin-dong Yang; Xiao-ru Sun; Hui Zhang; Wei Pan; Xing-ming Wang; Jian-jun Yang; Mu-huo Ji; Hong-mei Yuan (Molecular Neurobiology, 2016)

Antidepressant-like effects of standardized gypenosides: involvement of brain-derived neurotrophic factor signaling in hippocampus - Rong-Hao Mu; Xiao-Yan Fang; Shuang-Shuang Wang; Cheng-Fu Li; Shao-Mei Chen; Xue-Mei Chen; Qing Liu; Yu-Cheng Li; Li-Tao Yi (Psychopharmacology, 2016)

Development of a novel allele-specific Rfo marker and creation of Ogura CMS fertility-restored interspecific hybrids in Brassica oleracea - Hai-long Yu; Zhi-yuan Fang; Yu-mei Liu; Li-mei Yang; Mu Zhuang; Hong-hao Lv; Zhan-sheng Li; Feng-qing Han; Xiao-ping Liu; Yang-yong Zhang (Theoretical and Applied Genetics, 2016)

Association of Optic Radiation Integrity with Cortical Thickness in Children with Anisometropic Amblyopia - Shun Qi; Yun-Feng Mu; Long-Biao Cui; Rong Li; Mei Shi; Ying Liu; Jun-Qing Xu; Jian Zhang; Jian Yang; Hong Yin (Neuroscience Bulletin, 2016)

Enriched Environment Altered Aberrant Hippocampal Neurogenesis and Improved Long-Term Consequences After Temporal Lobe Epilepsy in Adult Rats - Xiaoqian Zhang; Tingting Liu; Zhike Zhou; Xiaopeng Mu; Chengguang Song; Ting Xiao; Mei Zhao; Chuansheng Zhao (Journal of Molecular Neuroscience, 2015)

Breeding of cabbage (Brassica oleracea L. var. capitata) with fusarium wilt resistance based on microspore culture and marker-assisted selection - Hong-hao Lv; Qing-biao Wang; Li-mei Yang; Zhi-yuan Fang; Yu-mei Liu; Mu Zhuang; Yang-yong Zhang; Yu-hong Yang; Bing-yan Xie; Xiao-wu Wang (Euphytica, 2014)

MiR-506 inhibits PRRSV replication in MARC-145 cells via CD151 - Junjing Wu; Xianwen Peng; Ao Zhou; Mu Qiao; Huayu Wu; Hongwei Xiao; Guisheng Liu; Xinmin Zheng; Shujun Zhang; Shuqi Mei (Molecular and Cellular Biochemistry, 2014)

Synthesis of novel isoquinolinone and 1,2-dihydroisoquinoline scaffolds via Ugi reaction and ring opening reaction of furans - Fei Ji; Wen-bin Yi; Mu Sun; Mei-fang Lv; Chun Cai (Molecular Diversity, 2013)

Identification of the promoter region and genetic mutations of the porcine GALP gene - Lina Su; Shuqi Mei; Hu Tao; Xianwen Peng; Xiaojie Sun; Huayu Wu; Xuying Zhang; Mu Qiao; Fenge Li (Molecular Biology Reports, 2013)

Effects of pH, MES, arabinogalactan-proteins on microspore cultures in white cabbage - Su-xia Yuan; Yan-bin Su; Yu-mei Liu; Zhi-yuan Fang; Li-mei Yang; Mu Zhuang; Yang-yong Zhang; Pei-tian Sun (Plant Cell, Tissue and Organ Culture (PCTOC), 2012)

Imprinting analysis of porcine DIO3 gene in two fetal stages and association analysis with carcass and meat quality traits - Mu Qiao; Hua-Yu Wu; Ling Guo; Shu-Qi Mei; Peng-Peng Zhang; Feng-E Li; Rong Zheng; Chang-Yan Deng (Molecular Biology Reports, 2012)

Combination of Hyaluronic Acid Hydrogel Scaffold and PLGA Microspheres for Supporting Survival of Neural Stem Cells - Ying Wang; Yue Teng Wei; Zhao Hui Zu; Rong Kai Ju; Mu Yao Guo; Xiu Mei Wang; Qun Yuan Xu; Fu Zhai Cui (Pharmaceutical Research, 2011)

Alternative splicing of the antitrypsin gene in the silkworm, Bombyx mori - Hui-fen Liu; Yi-nü Li; Ru Jia; Wei-zheng Cui; Zhi-mei Mu; Zhi-fang Zhang (Molecular Biology Reports, 2011)

Genetic polymorphism analysis of 15 STR loci in Chinese Hui ethnic group residing in Qinghai province of China - Ya-jun Deng; Bo-feng Zhu; Chun-mei Shen; Hong-dan Wang; Jing-feng Huang; Yuan-zhe Li; Hai-xia Qin; Hao-fang Mu; Jie Su; Jie Wu; Bo Zhang; Shuan-liang Fan (Molecular Biology Reports, 2011)

Effect of high glucose concentration on VEGF and PEDF expression in cultured retinal Müller cells - Hua Mu; Xiao-Mei Zhang; Jian-Ju Liu; Li Dong; Zhuo-Lei Feng (Molecular Biology Reports, 2009)

Antimicrobial activity of isolate HL-12 against Clavibacter michiganensis subsp. michiganensis in the presence of cadmium - Hai-ping Yuan; Hang Min; Zhen-mei Lv; Zi-mu Li (Ecotoxicology, 2009)

A GIS-based research on the distribution of rural settlements in Yulin of northern Shaanxi - Zhao Mu-dan; Tang Guo-an; Shi Wen-zhong; Liu Yong-mei (Journal of Geographical Sciences, 2002)